ANALISIS HAMBATAN KOLABORASI PEMERINTAH PADA IMPLEMENTASI KEBIJAKAN GEOPARK DIENG - Yasmin Wulansari; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2026)
The Dieng Geopark policy represents a governmental effort to promote area conservation through sustainable tourism by integrating conservation, education, and community economic development. However, the implementation of the Dieng Geopark policy involves multiple actors across sectors and administrative regions, thereby requiring effective collaboration among stakeholders. In practice, such collaboration faces various barriers that have the potential to affect policy effectiveness. This study aims to analyze the barriers to collaboration in the implementation of the Dieng Geopark policy and to examine their implications for the effectiveness of conservation policy. The research adopts a qualitative approach using a case study method. Data were collected through in-depth interviews, documentation, and literature review. Data analysis was conducted using the Collaborative Governance framework proposed by Ansell and Gash and the Stakeholder Salience theory developed by Mitchell, Agle, and Wood. The findings indicate that barriers to collaboration in the implementation of the Dieng Geopark policy are influenced by power imbalances among different levels of government, differences in stakeholder interests, and variations in perceived urgency toward the geopark policy. Power imbalances result in a predominantly hierarchical decision-making process, while differences in interests and urgency contribute to weak coordination, inconsistent implementation, and slow translation of policy into concrete actions on the ground. These barriers ultimately lead to the suboptimal achievement of integrated and sustainable conservation objectives within the Dieng Geopark policy.